Long-Term Follow-Up of Subjects Without Overt Heart Disease With an Early Repolarization/J Wave Electrocardiographic Pattern - Lanza, Gaetano Antonio; Melita, Veronica; De Vita, Antonio; Bisignani, Antonio; Mollo, Roberto; Crea, Filippo (Frontiers in Cardiovascular Medicine, 2022)
Aims. The “early repolarization” (ER) pattern and J wave are frequent findings on standard electrocardiogram (ECG). Controversial data have recently been reported about their prognostic implications in healthy subjects, but no longitudinal prospective study specifically designed to investigate their long-term prognostic value has hitherto been published. Methods and Results. We prospectively enrolled 4176 consecutive subjects with no evidence of cardiovascular disease who were referred for standard ECG recording for routine check-up or pre-operative assessment for non-cardiovascular surgery. ECGs were prospectively assessed for the presence of ER/J. Ten-year follow-up was available for 3937 patients (94.3%), 660 of whom (16.8%) showed ER/J wave whereas 3277 did not. A total of 644 deaths occurred (16.3%), 116 (2.95%) of which attributed to cardiovascular causes. Both total and cardiovascular mortality adjusted for clinical and laboratory variables did not differ significantly between patients with vs. without ER/J wave (HR 0.94; 95% CI 0.75-1.19; p=0.63 and HR 0.61; 95% CI 0.31-1.21; p=0.16, respectively). No significant association with total and cardiovascular mortality was also found in pre-specified analyses for ER and J wave alone, ER/J wave detected in specific ECG regions (i.e., inferior, lateral, precordial) and type of J wave (notched or slurred). Conclusion. In this specifically designed prospective study of individuals without any evidence of cardiovascular disease, we found no significant association of ER/J wave with the risk of total as well as cardiovascular mortality during long-term follow-up.